2015
DOI: 10.1007/s00586-015-3795-3
|View full text |Cite
|
Sign up to set email alerts
|

Fiber types of the anterior and lateral cervical muscles in elderly males

Abstract: Purpose: The anterior and lateral cervical muscles (ALCM) are generally considered to be postural, yet few studies have investigated ALCM fiber types to help clarify the function of these muscles. This study aimed to systematically investigate ALCM fiber types in cadavers.Methods: Anterior and lateral cervical muscles (4 scalenus anterior, medius, posterior muscles; 5 longus colli, 5 longus capitis taken bilaterally from one cadaver) were removed from four male embalmed cadavers (mean age 87.25 years). Paraffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another explanation for these different responses of the cervical and lumbar muscles could be related to their histophysiological characteristics. Although both cervical and lumbar muscles have a predominance of type I fibers, indicative of their postural character [ 38 , 39 ], it is known that there are differences between the muscles of different anatomical regions at the level of component molecules that reflect their differences in the development of active voltage, passive voltage and mechanosensitive signaling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for these different responses of the cervical and lumbar muscles could be related to their histophysiological characteristics. Although both cervical and lumbar muscles have a predominance of type I fibers, indicative of their postural character [ 38 , 39 ], it is known that there are differences between the muscles of different anatomical regions at the level of component molecules that reflect their differences in the development of active voltage, passive voltage and mechanosensitive signaling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inferiorly, it remains anterior to the anterior tubercles of the transverse processes, which allows it to be differentiated from longus colli and the scalenus muscles, particularly scalenus anterior (Fig. 2 ) [ 60 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…There was also no main effect of age; however, there was a significant main effect of group. In previous studies related to age reported that the proportion of Type I muscle fibers in the longus colli and longus capitis muscles in the elderly decreased compared to that of the scalene muscles 40) , and the antigravity muscle strength in the elderly decreased compared that in young individuals 41) . Conversely, the endurance of patients with neck pain is very low even among young people 42) .…”
Section: Discussionmentioning
confidence: 92%